2016
DOI: 10.3920/cep160015
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training-induced changes in the gut microbiota of Standardbred racehorses

Abstract: Exercise has a significant effect on different physiological systems in the body of human and animals. Only limited numbers of published studies in laboratory animals or humans have shown the effect of exercise on the gut microbiota, and no studies have shown this effect in horses. In this study, 8 horses (4 mares, 4 geldings) were exercise trained for 12 weeks, and 4 additional mares were used as a parallel seasonal control. To identify bacterial community changes over time for both groups, rectal faecal samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…Clostridium XIVa, Fibrobacter and Treponema genera were the most abundant genera, which is in agreement with a study in Standardbred racehorses by Janabi et al . 35 that showed that training led to an increase in Treponema and Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium XIVa, Fibrobacter and Treponema genera were the most abundant genera, which is in agreement with a study in Standardbred racehorses by Janabi et al . 35 that showed that training led to an increase in Treponema and Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results using the same horses have shown that 12 weeks of training significantly affects the gut microbiome (Janabi et al, 2016). Concomitant with changes in the gut microbiome, there was also a change in the skeletal muscle xenobiotic signature.…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, the samples collected at the beginning of the experiment and the end of the conditioning period were similar, suggesting that the population structure of the intestinal microbiota may have adapted after the aerobic conditioning period of 42 days. The return of the population structure to pre-training levels may indicate dormancy [31] or resilience of equine intestinal microbiota-related dysbiosis [32]. This suggests that changes in exercise may exert important influences on the microbiota rather than the absolute level of exercise or specific type of exercise.…”
Section: Discussionmentioning
confidence: 99%